Drama and Theatre Education in Canada: A snapshot - Carter, Mindy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2014)
This “Note from the Field” provides an overview of what is happening in K to University drama and theatre education across Canada. In addition to this snapshot I offer some considerations for extending this discipline and its potential impact on curriculum, policy and practice.